Islam Hadhari’s principles and reward management practices: A study in Malaysian private organizations - Wan Mohd Noor, Wan Shakizah; Quaddus, Mohammed; Whiteley, Alma; Mohd Isa, Mohd Faizal; Daud, Zulkiflee (2013)
This study is an attempt to provide further insights into the theory and practice of reward management in the local context as Malaysia is implementing Islam Hadhari’s principles in the country.This study also further investigates the relationship between Islam Hadhari’s principles and perceptions of non-monetary and monetary rewards toward the reward program influences.The study adopts a quantitative approach using Partial Least Square (PLS) based Structural Equation Modeling (SEM) approach.The study will benefit the human resource practitioners theoretically and practically by providing direction and suggestions in designing and implementing the non-monetary and monetary rewards for Malaysian private organizations from Islamic perspectives.